A Whisker-inspired Fin Sensor for Multi-directional Airflow Sensing - Kim, Suhan; Kubicek, Regan; Paris, Aleix; Tagliabue, Andrea; How, Jonathan P.; Bergbreiter, Sarah (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2020)
This work presents the design, fabrication, and characterization of an airflow sensor inspired by the whiskers of animals. The body of the whisker was replaced with a fin structure in order to increase the air resistance. The fin was suspended by a micro-fabricated spring system at the bottom. A permanent magnet was attached beneath the spring, and the motion of fin was captured by a readily accessible and low- cost 3D magnetic sensor located below the magnet. The sensor system was modeled in terms of the dimension parameters of fin and the spring stiffness, which were optimized to improve the performance of the sensor. The system response was then characterized using a commercial wind tunnel and the results were used for sensor calibration. The sensor was integrated into a micro aerial vehicle (MAV) and demonstrated the capability of capturing the velocity of the MAV by sensing the relative airflow during flight.